Analysis of regional differences, spatial-temporal characteristics, and influencing factors of the coupling and coordination development of science and technology innovation between universities and enterprises in China - Liu, Xiao; Wang, Qingjin; Gao, Hao; Cui, Qian (Frontiers in Earth Science, 2025)
IntroductionThe coupling and coordination development level (CCDL) of science and technology innovation (STI) between universities and enterprises is a key determinant of the effectiveness of the national STI system.MethodsThis study utilized data from universities and industrial enterprises spanning from 2012 to 2021 to establish an indicator system for measuring university STI ability and enterprise STI ability. The study then applied the entropy TOPSIS method to calculate the STI scores and further analyzed them using a coupling coordination model. Various research methods were employed to quantify the spatiotemporal characteristics and elucidate the patterns of evolution, with the grey relational analysis model being utilized to examine the mutual influence at the micro-index level.Results and discussionThe study found a significant transformation in the collaboration between universities and enterprises in China, shifting from extreme incoherence to highly coordinated cooperation. Secondly, the reason for the differences is the uneven development in the four regions. Thirdly, the CCDL of STI between universities and enterprises in each region is notably different, but all show σ convergence trend. Finally, the university STI ability and enterprise STI ability are identified as key factors in the CCDL of STI between universities and enterprises.